Online Reputation Management pada Bank Syariah Indonesia (BSI): Analisis Pengelolaan Media Sosial untuk Memperkuat Citra Syariah - Agnia Mumtaza; Shafira Rixas; Hana Afni; Abdurrahman Zavier; Muhammad Agung Dharmajaya (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
The rapid growth of social media has transformed the way organizations build and maintain their reputation in the digital era, particularly in the Islamic banking sector, where public trust is a fundamental asset. This study aims to analyze the Online Reputation Management (ORM) strategy implemented by Bank Syariah Indonesia (BSI) through social media management to strengthen its Islamic brand image. This research employed a descriptive qualitative approach using content analysis of BSI's official social media accounts as the primary data source, supported by secondary data from scholarly journals, books, company reports, and relevant literature. The findings reveal that BSI implements ORM through three main stages: prevention, reaction, and evaluation. The prevention stage is reflected in the consistent dissemination of educational, informative, and Sharia-based content. The reaction stage is demonstrated through responsive and interactive engagement with public comments and inquiries to maintain positive relationships with stakeholders. Meanwhile, the evaluation stage is evident in the consistency of visual identity, communication messages, and the representation of Islamic values across digital platforms. The study concludes that strategic, interactive, and sustainable social media management contributes significantly to building a positive online reputation while reinforcing BSI's Sharia image. These findings provide theoretical contributions to digital Public Relations and practical insights for Islamic banking institutions in managing online reputation in the digital environment.